Efektivitas Lucas NCT Sebagai Brand Ambassador Terhadap Keputusan Pembelian Produk Neo Coffee - Nyoman Setia Purnama Putra; Retno Lantarsih; Artita Devi Maharani (Fakultas Pertanian UST, 2022)
This study aimed to determine the effectiveness of using Lucas NCT as a brand ambassador in purchase decisions for Neo Coffee products. The basic method used was descriptive analytic. The study was carried out from December 2021 to 70 NCTZen respondents on instagram. Analysis was performed using the effectiveness formula, theory of planned behavior, and a simple linier regresion. The result showed that using Lucas NCT as Brand Ambassador was effective and significant as evidenced by the result of an average achievement of 77.89%, a simple linier regression of Y= 5.868 + 0.994x, with t value > t crit= 7.929 > 1.995, and significant of = 0.000, 0.05.